Sundial: A world-wide study of interactive ionospheric processes and their roles in the transfer of energy and mass in the sunearth system - Szuszczewicz, E. P. (1988)
During the period 5-13 October 1984 a coordinated solar-terrestrial data base was acquired to develop a comprehensive understanding and an associated predictive capability for the cause-effect relationships which control the global-scale ionosphere. The effort, the first in a series of continuing investigations in a program called SUNDIAL, combined modelling of the ionospheric, magnetospheric, and thermospheric domains with a measurements activity that included a network of ionospheric monitoring stations at high-, middle-, and low latitudes in the American, European/African, and Asian/Australian sectors. Solar, solar wind, interplanetary, and geomagnetic data were also obtained through the NOAA Space Environment Services Center. The period began with nearly two full days of typically quiescent solar mínimum conditions, with the night of the 6th marking a transition to a substantial increase in solar wind velocities, and enhanced dynamics in the interplanetary magnetic field with associated geomagnetic disturbances. The increased solar wind velocities resulted from a corotating high-speed stream coupled to a transequatorial solar coronal hole. Evidence points to a step-wise coupling of processes from the coronal hole through the interplanetary and magnetospheric domains down to the equatorial ionosphere, where penetrating electric fields participated in triggering the most disturbed condition of equatorial spread-F ever recorded by the Jicamarca Observatory. The correlation of events also included : (1) enhanced particle precipitation power at high latitudes, (2) an associated cross polar cap potential of 75 k Y, and (3) simultaneous global observations of F-region dynamics. In addition, detailed model comparisons with observations of the quiet and disturbed ionosphere point to requirements for improved global specification of thermospheric winds and electric fields. The content of this paper presents an overview of the program, its initial findings, recommendations, and future perspectives.